Penyelesaian Tindak Pidana Kekerasan Dalam Rumah Tangga Melalui Mediasi: (Studi di Polres Tanah Karo) - Eka Mei Riska Sitepu (Jurnal Hukum Lex Generalis, 2025)
Domestic violence cases are increasing, despite existing laws and regulations that serve as a legal umbrella to protect women's rights and dignity. However, this violence is very difficult to disclose because many parties consider violence to be a common occurrence. This study aims to analyze the implementation of mediation in handling domestic violence crimes at the Tanah Karo Police Station. The type of research used is empirical juridical with a qualitative descriptive research method with a case study approach. The results show that the resolution of domestic violence crimes through mediation is carried out using a restorative justice approach that aims to create peace between the victim and the perpetrator while still paying attention to the victim's rights. Mediation is very effective in resolving domestic violence crimes because this process poses a threat to the restoration of relationships and comprehensive justice, rather than simply imposing punishment.